Relevansi Kurikulum Madrasah Diniyah Takmiliyah dengan Keputusan Dirjen Pendis Nomor 3633 Tahun 2023 - Muhammad Ahsanun Ni’am; Reza Ahmad Zahid; Abbas Sofwan Matlail Fajar (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2026)
Education is a basic need for all human beings. This is because through education, a person can become a complete human being in terms of both knowledge and practice. In education, the role of the curriculum is considered the main foundation, because the success or failure of education depends on how the curriculum is organized and applied in learning. Therefore, the organization and development of the curriculum are needed so that the learning activities carried out can be maximized, achieve the desired targets, and suit the needs of students and the characteristics of the educational institution. The method used in this study is descriptive qualitative. Data and information collection techniques were carried out through observation, interviews, and documentation with triangulation as a data validation method. The purpose of this study was to identify the curriculum components in Islamic educational institutions such as madrasah diniyah takmiliyah and their implementation in learning, as well as to determine the relevance of the MDT (madrasah diniyah takmiliyah) curriculum to the Director General of Islamic Education Decree No. 3633 of 2023. The results of the study show that the curriculum components found in MDT include four components, namely objectives, teaching materials, learning methods or systems, and evaluation. The implementation of the curriculum is carried out in the form of curricular and extracurricular activities. Furthermore, the relevance of the MDT curriculum to the Director General of Islamic Education's Decree No. 3633 of 2023 can be seen in four aspects, namely objectives, materials, methods or systems, and evaluation.